DESKRIPSI KEMAMPUAN KOMUNIKASI MATEMATIS MATERI STATISTIKA DITINJAU DARI SELF-CONFIDENCE SISWA KELAS VIII SMP MUHAMMADIYAH LIMBUNG - Nur Ishlah AR; Ahmad Syamsuadi; Ernawati (Jurnal Penalaran dan Riset Matematika, 2023)
This study aims to determine and describe the mathematical communication skills of statistical material in terms of the self-confidence of class VIII students of SMP Muhammadiyah Limbung. This research is a descriptive qualitative approach. The subjects in this study were 6 students of class VIII-9 who were selected based on self-confidence grouping, namely 2 students who had high self-confidence, 2 students who had moderate self-confidence, and 2 students who had low self-confidence. The instruments used in this study were self-confidence questionnaires, mathematical communication skills tests, and interview guidelines. the data analysis techniques used are data condensation, data presentation, and data verification. The results show that: 1) Students who have high self-confidence, have an average mathematical communication ability of 91.67 which is included in the high category, based on indicators show that they are able to master written text, drawing and mathematical expressions indicators, 2) students who have moderate self-confidence, have an average mathematical communication ability of 45.8 which is included in the medium category, based on indicators showing that they are less able to master written text, drawing and mathematical expressions indicators and 3) students who have low self-confidence, have an average the average mathematical communication ability is 16.7 which is included in the low category, based on indicators showing that they are not able to master written text and mathematical expressions indicators, for drawing indicators.